2022
DOI: 10.4414/smw.2022.w30156
|View full text |Cite
|
Sign up to set email alerts
|

Confident and altruistic – parents’ motives to vaccinate their children against COVID-19: a cross-sectional online survey in a Swiss vaccination centre

Abstract: AIMS OF THE STUDY: In Switzerland, COVID-19 vaccines have been approved for children aged 5–11 years only recently, whereas vaccination of adolescents aged 12 years and older was approved in early summer 2021. Although the disease burden in children and adolescents has been reasonably mild, they can transmit COVID-19 to others, thus vaccinating this age group may help to curb the COVID-19 pandemic. The main objective was to investigate the association between five psychological antecedents of vaccination hesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
5
8
1
Order By: Relevance
“…Based on the centrality indices, it was shown that, among all variables, collective responsibility displayed the most connections to all other variables. Similar findings have been found in past research as well [ 63 , 64 , 65 ]. Overall, these findings illustrate the determining role of an internal feeling of collective responsibility in vaccine acceptance.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the centrality indices, it was shown that, among all variables, collective responsibility displayed the most connections to all other variables. Similar findings have been found in past research as well [ 63 , 64 , 65 ]. Overall, these findings illustrate the determining role of an internal feeling of collective responsibility in vaccine acceptance.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are also in line with those of previous studies showing that parental willingness to vaccinate their children decreased progressively with the age of the child, from 84.0% for parents of children aged 16-17 years to 19.5% for parents of children aged 5-11 years [8,[34][35][36]. However, in the studies from the US and Canada, these decreases were not as pronounced as in our findings [35,36].…”
Section: Original Articlesupporting
confidence: 92%
“…In a sample of Swiss Germanspeaking parents, 58.7% reported their intention to have their children vaccinated. However, this result might be overestimated because parents were recruited at a vaccination centre [34]. 1 Some data are excluded due to very low numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Trust in the COVID-19 vaccine [ 59 , 98 , 121 , 126 , 128 , 142 ], trust in governments [ 104 , 121 ], and trust to health system [ 60 , 63 , 72 , 80 , 89 ] were also contributing factors.…”
Section: Resultsmentioning
confidence: 99%
“…Obtaining influenza immunization was a positive contributing factor for parents to accept their children’s COVID-19 vaccination [ 57 , 59 , 65 , 68 , 77 , 86 , 104 , 116 , 121 , 140 ].…”
Section: Resultsmentioning
confidence: 99%